(untitled) (International Journal of Economics Management and Social Science, 2026)
This study examines the implications of global gold price volatility on nisab determination and zakat calculation methods from a contemporary fiqh mu’amalah perspective. Gold price fluctuations have created significant challenges in maintaining equitable zakat obligations, as traditional fixed-gram nisab thresholds may inadvertently burden lower-income Muslims during price spikes or reduce zakat collection during price drops. Using a qualitative approach with library research methodology, this study analyzes classical and contemporary fiqh literature, fatwas from various Islamic jurisprudence councils, and historical gold price data from 2015 to 2024. The research synthesizes scholarly opinions across different madhhabs regarding appropriate calculation methodologies in dynamic market conditions. Findings reveal three primary approaches emerged from contemporary ijtihad: first, maintaining fixed gram-based nisab with periodic review mechanisms; second, implementing currency conversion methods with regular benchmark adjustments; and third, utilizing averaged gold prices over specific timeframes to smooth volatility impacts. The study demonstrates that the Hanafi school’s interpretation offers greater flexibility for contemporary application, while Shafi’i and Maliki positions emphasize wealth preservation principles. Results indicate that volatile gold markets between 2020-2024 caused nisab values to fluctuate between forty-three to seventy-eight percent, significantly affecting muzakki populations and zakat revenue streams in Muslim-majority countries. The research concludes that contemporary nisab determination requires balancing three foundational Islamic principles: justice in obligation distribution, ease in compliance, and maximization of social welfare. Keywords: Gold Zakat, Nisab Threshold, Price Volatility, Contemporary Fiqh, Islamic Economics, Wealth Redistribution, Ijtihad